Chondrocutaneous Custom-made Graft for Upper Lateral and Alar Cartilage Nose Reconstruction: The T Graft - Vania Recchi; Alberto Pau; Davide Talevi; Simone Russo; Matteo Torresetti; Giovanni Di Benedetto (Archives of Plastic Surgery)
Upper lateral cartilage and alar cartilage nose reconstruction secondary to failed aesthetic procedure or tumor excision, surely represents a reconstructive challenge for plastic surgeons, because of the support needed and for the function of the internal nasal valve (INV).